2021
DOI: 10.3390/ijms22168373
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Glycine Reduce Uterus Ischemia/Reperfusion Injury in a Rat Model of Warm Ischemia

Abstract: Ischemia/reperfusion injury (IRI) remains a significant problem to be solved in uterus transplantation (UTx). Melatonin and glycine have been shown to possess direct cytoprotective activities, mainly due to their antioxidative and anti-inflammatory properties. The aim of this study was to investigate the protective effects of melatonin and glycine and their combination on IRI in a rat model of warm ischemia. In this study, Sprague-Dawley rats were assigned to eight groups, including sham and IRI (n = 80). Mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
3
1
0
Order By: Relevance
“…Several studies mentioned the protective properties of glycine in other organs such as the heart, kidney, uterus, liver, and skeletal muscle. 47,[104][105][106][107] In line with previous investigations on the antioxidative stress properties of glycine, we found that this amino acid significantly decreased oxidative stress biomarkers in Pb-treated animals. These studies indicate that the effects of glycine on oxidative stress parameters play a fundamental role in its protective properties.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies mentioned the protective properties of glycine in other organs such as the heart, kidney, uterus, liver, and skeletal muscle. 47,[104][105][106][107] In line with previous investigations on the antioxidative stress properties of glycine, we found that this amino acid significantly decreased oxidative stress biomarkers in Pb-treated animals. These studies indicate that the effects of glycine on oxidative stress parameters play a fundamental role in its protective properties.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the antioxidants levels were significantly higher in glycine‐treated groups (Figure 4). Several studies mentioned the protective properties of glycine in other organs such as the heart, kidney, uterus, liver, and skeletal muscle 47,104–107 . In line with previous investigations on the antioxidative stress properties of glycine, we found that this amino acid significantly decreased oxidative stress biomarkers in Pb‐treated animals.…”
Section: Discussionsupporting
confidence: 91%
“…In essence, the same results were achieved by Atalay et al by continuously administering remifentanil during ischemia-reperfusion [20]. Recently, the use of melatonin and glycine was shown to significantly reduce tissue MPO expression and increased SOD activity [21].…”
Section: Discussionsupporting
confidence: 53%
“…Warm ischemia can cause permanent damage if it lasts more than 4 h. Within 3 h, there were no histological or functional injuries, and these results that are transposable to the humans. In rats, the injection of Melatonin and Glycine ( 42 ), Remifentanil ( 41 ), or cannabinoid agonist JWH-133 ( 43 ) reduced warm ischemia-reperfusion injuries.…”
Section: Basic Researchmentioning
confidence: 99%